Network basics - Al Taie, M. Z. (Springer London, 2017)
This chapter introduces the concept of a network, which is obviously the core object of network analysis. We will discuss topics such as types of networks, network measures, installation and use of NetworkX library, network data representation, basic matrix operations, and data visualization. What Is a Network? A network can be a specialized type of mathematical graph or interconnected systems. Hence, it is not far from a graph, which implies the visual representation of a set of nodes and edges. Network nodes may represent web pages, people, organizations, articles, places, and many other things.